Analisis kemampuan scientific literacy siswa SMA dalam soal PISA pada materi virus dan bakteri - Fadillah, Nuke Siti; Rustaman, Nuryani; Kusumawaty, Diah (Department of Biology Education, Universitas Pendidikan Indonesia, 2021)
This study aims to analyze the scientific literacy skills of high school students on PISA released items reading and science questions based on the PISA framework on the